Thermodynamic analysis on wetting properties of a droplet on a solid surface with engineered trapezoidal microarchitecture. (April 2018) - He, Liang; Liang, Wenyan; Akbarzadeh, Abdolhamid
Graphical abstract: Highlights: A 3-D model for analyzing the wetting behavior of trapezoidal microarchitected surfaces is proposed. The effects of trapezoid base angle and base spacing on the superhydrophobicity are investigated. The three-phase contact line tension is taken into consideration for a droplet in composite state. Abstract: The wetting properties of a hydrophobic solid surface containing an engineered trapezoidal microarchitecture have been investigated based on a 3-D thermodynamic model. The three-phase contact line tension is introduced in the present approach for a droplet in the composite state, and the relationship between surface topology and superhydrophobicity is established. It is demonstrated that both trapezoid base angle and base spacing have great influence on the wetting transition between composite and non-composite states. Some recommendations are made for fabricating ideal superhydrophobic surfaces with optimal geometries. The validity of the present theoretical results has also been verified by comparing our theoretical predictions and experimental data available in the literature. The developed model in this paper sheds lights on the wetting properties of advanced materials with engineered microarchitecture.